Traumatic tension pneumocephalus: a case report and perspective from Indonesia - Harlyjoy, Alphadenti; Nathaniel, Michael; Nugroho, Aryandhito Widhi; Gunawan, Kevin (Frontiers in Neurology, 2024)
Traumatic tension pneumocephalus is a rare and life-threatening complication of traumatic brain injury necessitating prompt diagnosis and neurosurgical treatment. Nevertheless, various possibilities for impedance in timely management, including patient-related barriers are commonly experienced in low-and middle-income countries setting. Here we presented a delay of management in traumatic tension pneumocephalus case due to initial refusal for emergency surgery. A 59-year-old male presented to the emergency department following a motorcycle accident fully alert with no neurological deficit. He acknowledged clear nasal discharge within 1 hour after the initial trauma, but no rhinorrhea or otorrhea was present during physical examination. Head CT revealed extensive pneumocephalus with "Mount Fuji sign", anterior skull base fracture, and frontal sinus fracture. The patient initially refused immediate surgical intervention due to excellent clinical condition and financial scare. Acute decrease of consciousness occurred 40 hours post-trauma: GCS of 6 with slight dilatation of both pupils (4 mm) and sluggish pupillary reflex. Emergency bifrontal craniotomy, subdural air drainage, and dura mater tear repair were performed afterwards. Postoperative care was uneventful, with rapid improvement of consciousness and follow-up head CT showing minimal subdural fluid collection and absence of remaining pneumocephalus. The patient was discharged from the hospital after 7 days with GCS of 15 and GOS of 5, proving the importance of overcoming barriers for delay in delivering neurotrauma care in low-and middle-income countries.